Indian Cloud Computing Research: A Scientometric Assessment of Publications Output During 2004-13 - Gupta, B. M.; Gupta, Ritu (Journal of Information and Knowledge, 2015)
The paper is the result of the examination of 1206 publications on Indian cloud computing research, as covered in Scopus database during 2004-13, experiencing an annual average growth rate of 25.51% during 2008-13 and citation impact per paper of 11.69. The world cloud computing research output (21316 publications) came from several countries, of which the top 10 countries (China, USA, Germany, India, UK, Taiwan, Australia, Italy, Japan etc) accounted for 80.57% share of the global output during 2004-13. The major institutional contribution to cloud computing research comes from universities, followed by engineering colleges, institutes of national importance, industrial enterprises and research institutes during 2004-13. India’s global publication share was 5.66% and occupied 4th rank in global publication output during 2004-13. The Indian cloud computing output comes from several organizations and authors, of whom the top 15 and 10 authors contributed 33.25% and 7.30%, share respectively during 2004-13. India’s international collaborative share in cloud computing was 11.69% during 2004-13. Computer science accounted for the largest publication share (79.44%) of the output in cloud computing, followed by engineering (22.80%), mathematics (7.30%), social science (2.57%), etc during 2004-13. Suggest the need for the development of a cloud economy and the adoption of cloud services and build suitable policy and regulation to encourage migration of IT services towards the cloud.